Diagnosis and Treatment of Biliary Fistulas in the Laparoscopic Era - M. Crespi; G. Montecamozzo; D. Foschi (Gastroenterology Research and Practice)
Biliary fistulas are rare complications of gallstone. They can affect either the biliary or the gastrointestinal tract and are usually classified as primary or secondary. The primary fistulas are related to the biliary lithiasis, while the secondary ones are related to surgical complications. Laparoscopic surgery is a therapeutic option for the treatment of primary biliary fistulas. However, it could be the first responsible for the development of secondary biliary fistulas. An accurate preoperative diagnosis together with an experienced surgeon on the hepatobiliary surgery is necessary to deal with biliary fistulas. Cholecystectomy with a choledocoplasty is the most frequent treatment of primary fistulas, whereas the bile duct drainage or the endoscopic stenting is the best choice in case of minor iatrogenic bile duct injuries. Roux-en-Y hepaticojejunostomy is the extreme therapeutic option for both conditions. The sepsis, the level of the bile duct damage, and the involvement of the gastrointestinal tract increase the complexity of the operation and affect early and late results.